Prevalence of disordered eating in adults with gastrointestinal disorders: A systematic review. Issue 8 (7th October 2021) - Peters, Jessica E.; Basnayake, Chamara; Hebbard, Geoffrey S.; Salzberg, Michael R.; Kamm, Michael A.
Abstract: Background: Patients with gastrointestinal disorders are prone to heightened awareness of dietary intake. When diet‐related thoughts or behaviors are excessive, they may lead to psychological distress, nutritional compromise, and impair medical treatment. Identification of disordered eating behavior and eating disorders is crucial for effective management, but data on their prevalence within this population remain scarce. We conducted a systematic review of the prevalence of disordered eating behavior and eating disorders in adults with gastrointestinal disorders. Methods: MEDLINE, PubMed, and PsycInfo databases were searched up to June 2021. Studies examining disordered eating in adult patients with a primary gastrointestinal diagnosis were included. Key Results: A total of 17 studies met the inclusion criteria for the review. The range of gastrointestinal disorders examined included disorders of gut‐brain interaction (DGBI), coeliac disease, and inflammatory bowel disease (IBD). The methods for examining disordered eating were highly variable. The prevalence of disordered eating ranged from 13–55%. The prevalence was higher in patients with disorders of gut‐brain interaction (DGBI) than in those with organic gastrointestinal disorders. Factors associated with disordered eating included female sex, younger age, gastrointestinal symptom severity, anxiety and depression, and lower quality of life. Conclusions & Inferences: Disordered eating is highly prevalent in adult patients with gastrointestinal illness, particularly those with DGBI. Understanding whether a patient's primary underlying diagnosis is that of an eating disorder or gastroenterological disorder remains a challenge for clinicians. There is an unmet need to identify at‐risk patients so that psychological intervention can be included in the therapeutic strategy. Abstract : Process and summarized findings of a systematic review on disordered eating in adults with gastrointestinal disorders.